Studi Komparasi Pengalaman Menginap Tamu pada Hotel Kabin Area Perkotaan dan Kawasan Wisata Kota Bandung - Rosdiana, Rahma; Ersy Ervina; Tito Pandu Raharjo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cabin and low budget hotels are in great demand today, both in urban areas and in tourist areas. Although much in demand, until now there has been no research that measures how the experience of staying in urban areas and tourist areas compares. This study aims to analyze the guest's stay experience at the cabin hotel by comparing the two objects so that it can be used as an evaluation for the cabin hotel management to further improve service quality in providing a good stay experience. The approach used in this study is descriptive quantitative with cross-tabulation data analysis (Crosstab) assisted by SPSS version 25.0 software. By measuring the stay experience based on customer experience indicators consisting of sensor experience, emotional experience, and social experience. In cabin hotels, the results of research felt by tourists show that the experience of staying at cabin hotels in urban areas is more dominant in the sensor experience indicator, while in tourist area cabin hotels it is more dominant in the emotional experience indicator. For future researchers, the researcher suggests adding other variables and taking samples with a wider scope to maximize the quality of services provided for a better and memorable stay experience. And provide training to staff in terms of superior service such as improving interpersonal skills and being responsive to guest needs.